The Chilean territory in epic poetry of the XVI century: an imaginary of the challenges of the conquest of Arauco (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The aim of this article is to review and to analyze the passages relating to the Chilean territory in the epic poems that reported Arauco's War in the 16th century. Even if their central argument consisted of the warlike events, some passages gave content to the description of the space as an epic landscape. As it will be demonstrated, the representation of the territory not only was formed attending to the physical conditions of the land, but also to the literary resources of the epic that characterized to the south of Chile as a challenging and dangerous scene, historical and simultaneously literary space, representative of the heroic and indomitable condition of the Kingdom of Chile.
Keywords: Literary landscape; chilean territory; epic poetry; conquest of Chile